PRESUPPOSITION AND COMMON GROUND IN GRETA THUNBERGS SPEECH ON TACKLING CLIMATE CHANGE AT THE YOUTH4CLIMATE CONFERENCE 2021 - Mubarak, Hilwa; Rejeki, Sari; Setyowati, Agnes (Universitas Pakuan, 2022)
The objectives of this study are to analyze the presuppositions and common ground in Greta Thunbergs speech at the 2021 Youth4Climate conference. This study uses the descriptive-qualitative method. By using Yules theory, the utterances in Thunbergs speech were analyzed into presupposition types. The classification of presuppositions helps to conclude the background belief, relating to an utterance that must be mutually known or assumed by the speaker and addressee. The results reveal that all types of presupposition exist in Thunbergs utterances. The presuppositions are related to the tackling of climate change by world leaders. The common ground also illustrates a similar issue.Keywords: presupposition; presupposition types; common ground; climate change.